2020
DOI: 10.1155/2020/8475840
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Autophagy‐Related Markers Bclin‐1 and LC‐3 in Colorectal Cancers: A Systematic Review and Meta‐analysis

Abstract: Objective. At present, the relationship between autophagosomes and the prognosis of various cancers has become a subject of active investigation. A series of studies have demonstrated the correlation between autophagy microtubule-associated protein light chain 3 (LC-3), Beclin-1, and colorectal cancer (CRC). Since autophagy has dual regulatory roles in tumors, the results of this correlation are also uncertain. Hence, we summarized the relationship between Beclin-1, LC-3, and CRC using systematic reviews and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
(45 reference statements)
2
6
0
Order By: Relevance
“…The findings of the present study indicated that LC3 overexpression was positively associated to lymph node metastasis in CC. Similar to the results of Li et al ( 23 ), the present study also suggested that LC3 was a protective marker for patients with CC. In total, nine studies were included by Li et al ( 23 ), and only six of the studies were associated with LC3 expression.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of the present study indicated that LC3 overexpression was positively associated to lymph node metastasis in CC. Similar to the results of Li et al ( 23 ), the present study also suggested that LC3 was a protective marker for patients with CC. In total, nine studies were included by Li et al ( 23 ), and only six of the studies were associated with LC3 expression.…”
Section: Discussionsupporting
confidence: 92%
“…Alkaline phosphatase (ALP), as an indicator of the early differentiation of osteoblasts, is closely associated with bone tissue remodeling and bone matrix mineralization [ 44 ]. The high levels of ALP expression indicate the ongoing differentiation of osteoblasts and the maturity of bone tissue [ 45 ]. In osteogenesis, the main effect of metformin is acting on AMPKa, upregulating the expression of RUNX2, and promoting the secretion of ALP [ 16 ].…”
Section: The Potential Mechanism Of Metformin On Diabetic Bone Improv...mentioning
confidence: 99%
“…In addition, the level of autophagy is higher in metastatic melanoma compared with primary tumor (42). In a previous study, UCHL3 knockdown increased the number of autophagosomes on examination of the ultrastructure of melanoma cells, which was associated with a notable increase in LC3B levels and the LC3II/LC3I ratio (43). The results of the present study suggest that the increase in autophagy level may be an important factor mediating the inhibitory effects of UCHL3 knockdown on the biological activity of melanoma cells.…”
Section: Discussionmentioning
confidence: 80%